Analytical Modeling and Results Evaluation of Composite Open Web Steel Joists Behavior - Hadeed, Ali Farhan; Al-Hadithy, Laith Khalid; Aziz, Riyadh J. (Al-Nahrain Journal for Engineering Sciences, 2018)
In this study, the analytic model (Azmi Model) had been considered for computation the load capacities of the composite open web steel joists and compared them with those obtained from experimental tests. The capacities of seven joists had been studied, each including one of the following variables (distribution of headed studs, connection degree of the connectors, inclination of the web, shape of the web, density of slab concrete, length of connectors).Theoretically, according to the Analytic model, the referenced joist of (45° web inclination , uniformly distributed ,over connected ,short headed studs) exhibited maximum load capacity of (18.45) ton, while the joist of (45° web inclination, uniformly distributed, under connected, short headed studs) exhibited minimum load capacity of (16.23) ton at yield point of bottom chord. Experimentally, the referenced joist exhibited maximum load capacity of (15.51) ton, while the joist of (34° web inclination, uniformly distributed, over connected, short headed studs) exhibited (12.49) ton load capacity. The load capacities values of the tested joists ranged between (67%-85%) of the predicted values according to the analytic model.